The Growth of Mullets (Mugil dusemmerie) Seeds was Observed from the Provision of Different Types of Feed - T. Zulkhaidir Zulkhaidir (Central Research Institute For Agriculture, 2021)
The purpose of this study was to determine the effect of giving tempuyung crude extract with different concentrations on the survival rate of carp infected with Aeromonas hydrophila bacteria. The purpose of this research is as a source of information for entrepreneurs and fish farmers which can be used as an alternative ingredient to treat fish that are attacked by diseases caused by the bacterium Aeromonas hydrophila. The results showed that administration of tempuyung crude extract (Sonchus arvensis L.) with different doses had a significant effect on the survival rate of carp (Cyprinus carpio L.) infected with Aeromonas hydrophila bacteria, this means rejecting Ho and accepting H1. The BNT test results showed that treatment A (3%) gave the highest survival rate of 93.33%, followed by treatment B (6%) of 73.33%, then treatment C (9%) and D (12%) of 60%. While the K treatment (control) was 20%. The relationship between the concentration of tempuyung crude extract and the survival rate of carp is in the form of a quadratic line equation Y = – 1.1 X² + 14.89 X + 31.996 with R2 = 0.672 and r = 0.82. The higher the dose of antibacterial used, the faster the bacterial cells will be killed. But it is not effective to use doses that are too high in treatment. Besides causing bacterial resistance to certain antibacterials, the use of doses that are too high can kill the host (goldfish) and is also less economical to use.